2019
DOI: 10.1159/000499066
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β42 and Total Tau Levels in Cerebrospinal Fluid Associate with Survival in an 85-Year-Old Population-Based Cohort Followed until Death

Abstract: Background: Dementia of Alzheimer’s type (AD) is related to decreased survival. It is not clear whether also biological markers of AD are related to mortality. Low levels of amyloid beta-42 (Aβ42) and high levels of total tau (T-tau) protein in cerebrospinal fluid (CSF) are established biomarkers for AD. Objective: Our aim was to investigate whether levels of Aβ42 and T-tau are associated with survival among octogenarians independently of dementia status. Methods: Sixty-five 85-year-olds underwent lumbar punct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Studies that examined the association between individual CSF biomarkers of AD and mortality have shown contrasting results; some have reported an association with CSF tau [ 18 , 27 ] and hyperphosphorylated tau [ 17 ], while others did not find an association [ 18 , 27 , 28 ]. As in the present study, most studies found a lower level of CSF Aβ42 to be associated with a higher risk of mortality [ 18 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 79%
“…Studies that examined the association between individual CSF biomarkers of AD and mortality have shown contrasting results; some have reported an association with CSF tau [ 18 , 27 ] and hyperphosphorylated tau [ 17 ], while others did not find an association [ 18 , 27 , 28 ]. As in the present study, most studies found a lower level of CSF Aβ42 to be associated with a higher risk of mortality [ 18 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 79%
“…Older adults are at a greater risk for abnormal Aβ and tau. Memory declines in older adults without dementia, and deposition of Aβ and tau normally increases with age 4. In addition, Ribbe et al4 reported that the life span of people 85 years or older with abnormal Aβ and tau levels was shortened by 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…Older adults are at a greater risk for abnormal Aβ and tau. Memory declines in older adults without dementia, 4 In addition, Ribbe et al 4 reported that the life span of people 85 years or older with abnormal Aβ and tau levels was shortened by 1 year. Improved Aβ and tau levels have been reported with consumption of green tea more than 3 times each week, 18 an effect more pronounced in people between the ages of 65 and 74 years.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations